Theorising practices of inclusive pedagogy: a challenge for initial teacher education - Mulholland, M; Thompson, I; Todd, J (Routledge, 2022)
This chapter addresses some of the tensions and challenges involved in practical theorising on inclusive pedagogy within the contexts of the contradictions found around issues of inclusion and special needs and disabilities policy and practice. One of the problems of focusing on inclusive pedagogy within initial teacher education is that has been hard to specify what inclusive practices in the classroom actually look like and how they might differ from pedagogical practice or reflective practice in general. Practical theorising combined with insights from inclusive pedagogy offers an approach that focuses on the student-teachers’ acquisition of adaptive skills, developed and underpinned by careful scrutiny of the ideas offered to them. Student-teachers working in special school settings can develop the flexibility, creativity and resilience to extend their knowledge and understanding of pedagogy, to sharpen their forensic teaching skills and to participate in inquiry-based practice to find the best way forward for the individual children and young people whom they teach.